2021
DOI: 10.1186/s12931-021-01632-z
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG16 promotes pulmonary fibrosis by targeting miR-455-3p to regulate the Notch2 pathway

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is the most common interstitial lung diseases with a poor prognosis. Long non-coding RNAs (lncRNAs) have been reported to be involved in IPF in several studies. However, the role of lncRNA SNHG16 in IPF is largely unknown. Methods Firstly, experimental pulmonary fibrosis model was established by using bleomycin (BML). Histology and Western blotting assays were used to determine the different stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…For example, lncRNA Hoxaas3 accelerates pulmonary fibrosis by targeting the miR-450b-5p/Runx1 axis ( 22 ). Liu et al found that lncRNA SNHG16 also functions as a promoter in pulmonary fibrosis via the modulation of the Notch2 pathway ( 12 ). Sun et al showed that lncRNA pulmonary fibrosis inhibitor (PFI) ameliorates pulmonary fibrosis by binding to splicing regulator Serine/arginine-rich splicing factor 1 (SRSF1) ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lncRNA Hoxaas3 accelerates pulmonary fibrosis by targeting the miR-450b-5p/Runx1 axis ( 22 ). Liu et al found that lncRNA SNHG16 also functions as a promoter in pulmonary fibrosis via the modulation of the Notch2 pathway ( 12 ). Sun et al showed that lncRNA pulmonary fibrosis inhibitor (PFI) ameliorates pulmonary fibrosis by binding to splicing regulator Serine/arginine-rich splicing factor 1 (SRSF1) ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNAs have been shown to have important functions in the pathogenesis of systemic sclerosis, dermatomyositis, and cutaneous lupus erythematosus (11). Notably, lncRNAs have been shown to participate in pulmonary fibrosis (12)(13)(14). Lnc-NONHSAT071210 is a novel lncRNA on which little research has been conducted to date.…”
Section: Introductionmentioning
confidence: 99%
“…SNHG16 is an important tumour-associated lncRNA that regulates many miRNAs, including miR-216-5p [148], miR-455-3p [149], and miR-605-3p [150]. A 7571bp region encodes it on chromosome 17q25.1.…”
Section: Snhg16mentioning
confidence: 99%
“…Increasing evidence shows that long noncoding RNAs (lncRNAs) have an important influence on PF [ 12 , 13 ]. Gokey et al [ 14 ] showed that in IPF epithelial cells, the most improved lncRNA is lncRNA maternally expressed gene 3 (MEG3), which plays an important role in regulating the function of basic progenitor cells.…”
Section: Introductionmentioning
confidence: 99%